Auto-Dissemination of Beauveria Bassiana in Controlling Coffee Berry Borer - Endang Sulistyowati; Dwi Suci Rahayu; Merle Shepard; Gerry Carner (Indonesian Coffee and Cocoa Research Institute, 2017)
Coffee berry borer (CBB), Hypothenemus hampei Ferr. (Coleoptera, Scolytidae) is generally controlled by applying integrated pest management, particularly through sanitation and using biological agents. Beauveria bassiana is wellknown as an entomopathogenic fungus, which has been proven to be the most effective and prospective agent that could be developed to control CBB. Dissemination of microbial biocontrol agents via insect or predators may has advantages for safe spore dispersal to targeted pests with the added benefit of predation. The research with aim to determine if spores of B. bassiana can be picked up by CBB from disseminated containers had been conducted at Plant Protection Laboratory and Kaliwining Experimental Station of Indonesian Coffee and Cocoa Research Institute. Ten infected coffee berries and ten CBB adults were sprayed with various concentration of B. bassiana suspension, and then infested them in 10 healthy berries in petridish. The same trials was conducted in the field, by infested them to healthy berries on coffee branches. Observation was done on the percentage of infected berries and number of CBB infected by B. bassiana inside the berries. The results showed that spores of B. bassiana could be picked up by CBB from disseminated containers, although it was very low (2.5%). B. bassiana was not effective in suppressing CBB infestation by auto-dissemination, therefore to improve the effectiveness of B. bassiana in controlling CBB, it was advised to re-spray at least 3 times in every cropping season, especially at the flying time of CBB around 2 P.M.